Robot-Assisted Laparoscopic IVC Treatment Strategy in Retroperitoneal Tumors - Liu, Lei; Tang, Shiying; Liu, Zhuo; Liu, Cheng; Zhang, Hongxian; Tian, Xiaojun; Wang, Guoliang; Zhang, Shudong; Ma, Lulin (Frontiers in Oncology, 2022)
ABSTRACT Objectives: To show the practice of robot-assisted laparoscopic inferior vena cava (IVC) treatment strategies in patients with retroperitoneal tumors. Patients and methods: From October 2020 to July 2021, 17 patients with retroperitoneal tumors successfully underwent robot-assisted laparoscopic tumor resection with IVC management. The patient details, tumor characteristics, intraoperative data, pathological features and severe complications were assessed. The IVC treatment strategies were divided into 4 ways: ①local resection and primary repair of the IVC; ②IVC ligation; ③ IVC reconstruction by bovine pericardial grafts; and ④ IVC transection and anastomosis. Results: In terms of IVC management, 5 cases had conventional total occlusion of the IVC and its branches, 3 cases had delayed occlusion of the proximal IVC technique, 2 cases had IVC resection by Satinsky clamp, 5 cases had IVC ligation, 1 case had IVC reconstruction by bovine pericardial grafts and 1 case had IVC transection and anastomosis. The median operation time was 151 min, and blood loss was 500 ml. There was no severe complication perioperatively. The follow-up time of 17 patients was 8 to 17 months (median: 12 months). No local recurrence or overall death was found during follow-up. Conclusions: These robot-assisted laparoscopic IVC treatment strategies were considered to be safe and feasible in experienced centers, as well as helpful to completely remove the tumor for better oncological prognosis and restore the blood reflux of IVC as much as possible to ensure fewer postoperative complications.